2008
DOI: 10.1159/000151243
|View full text |Cite
|
Sign up to set email alerts
|

The Principle of Homologous Groups in Regulatory Affairs of Allergen Products – A Proposal

Abstract: Among other legal regulations, the Note for Guidance on Allergen Products CPMP/BWP/243/96 released by the European Medicines Agency provides regulatory instructions regarding the quality of allergen extracts for diagnostic or therapeutic purposes. The current revision of this guideline intends to transform the so-called ‘principle of taxonomic families’ to the ‘principle of homologous groups’. According to this concept, the data of one allergen extract demonstrating stability, efficacy and safety can, to a lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
75
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 249 publications
(126 reference statements)
5
75
0
7
Order By: Relevance
“…Several publications have described the lack of group 2 and 5 allergens in C dactylon [16], although they are mentioned in Allergome. Only Cyn d 1 and Cyn d 7 have been found to exhibit some cross-reactivity with other grasses, but the results are not consistent [9]. Moreover, group 1 allergens in C dactylon have different epitopes to group 1 allergens in Pooideae grasses [1,17].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several publications have described the lack of group 2 and 5 allergens in C dactylon [16], although they are mentioned in Allergome. Only Cyn d 1 and Cyn d 7 have been found to exhibit some cross-reactivity with other grasses, but the results are not consistent [9]. Moreover, group 1 allergens in C dactylon have different epitopes to group 1 allergens in Pooideae grasses [1,17].…”
Section: Introductionmentioning
confidence: 91%
“…Membership of this group is based on the presence of 3 allergen families: group 1, 2, and 5 [9]. Cross-reactivity studies with different species have shown that the majority of Pooideae species are highly cross-reactive [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are nearly 30 kinds of allergenic components in HDM that have been cloned and identified (7). Approximately 80% to 100% of HDM allergic patients respond to group 1 and group 2 allergens (8).…”
Section: Introductionmentioning
confidence: 99%
“…At least 22 allergenic components in house dust mites have been cloned and identified (4). Among them, more than 80% of the HDM-allergic children with asthma have positive skin test reactions to group 1 and group 2 (Der p 1 and Der p 2) (5).…”
Section: Introductionmentioning
confidence: 99%